2020
DOI: 10.1590/1807-1929/agriambi.v24n1p65-71
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of soybean seeds inoculated with Bacillus subtilis strains

Abstract: The use of growth-promoting bacteria can increase the yield and quality of seeds of several annual crops, such as soybean. Based on that, the present study aimed to evaluate the effects of the inoculation of Bacillus subtilis strains on seed treatment, evaluating the yield and quality of seeds of two soybean cultivars. The experiment was conducted in a conventional system, in an Oxisol of clayey texture, in a crop under sprinkler irrigation. The experimental design was randomized blocks, arranged in split plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Although not all applied bio-inoculants resulted in an increase in 100-seed weight, Biofix, Masterfix, Nitrofix, and NitroZam gave higher values than the control in Angonia. The a pplication of bio-inoculants in soybean has been reported to result in increased seed quality and weight that positively increases yield (Gitonga et al, 2011;Tavanti et al, 2020). On the other hand, environment and variety interaction affected 100-seed weight, seeds pod −1 , and pods plant −1 (Table 8).…”
Section: Economic Importance Of Bio-inoculants For Soybean Productionmentioning
confidence: 99%
“…Although not all applied bio-inoculants resulted in an increase in 100-seed weight, Biofix, Masterfix, Nitrofix, and NitroZam gave higher values than the control in Angonia. The a pplication of bio-inoculants in soybean has been reported to result in increased seed quality and weight that positively increases yield (Gitonga et al, 2011;Tavanti et al, 2020). On the other hand, environment and variety interaction affected 100-seed weight, seeds pod −1 , and pods plant −1 (Table 8).…”
Section: Economic Importance Of Bio-inoculants For Soybean Productionmentioning
confidence: 99%
“…For example, under tropical conditions, Bacillus subtilis inoculation (strains Pant001 and QST713) associated with Bradyrhizobium japonicum has been reported to increase soybean [Glycine max (L.) Merr.] yield compared to single inoculation with B. japonicum, besides improving seed quality due to the increase in total storage proteins concentration, seedling emergence percentage and seed vigor (Tavanti et al, 2020). Traoré et al (2016) reported improved corn seed germination, plant growth, plant production (increase yield by 42%) grain and shoot P biomass content of 34 and 64%, respectively with B. subtilis inoculation (strain DSM10).…”
Section: Introductionmentioning
confidence: 99%
“…and Pseudomonas spp. as beneficial PGPB are being conducted, especially for annual crops (Oliveira et al, 2019;Pankievicz et al, 2019;Tavanti et al, 2020). For example, under tropical conditions, Bacillus subtilis inoculation (strains Pant001 and QST713) associated with Bradyrhizobium japonicum has been reported to increase soybean [Glycine max (L.) Merr.]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the bacteria of this genus can be consider plant growth promoting rhizobacterium (PGPR), because they can colonize the rhizosphere and promote plant growth (KALAM et al, 2020;TAVANTI et al, 2020). Rhizobacteria are essential for nutrient recycling and have potential as biofertilizers (SANTOS et al, 2020) for productivity increment, besides being able to benefit the plant during periods of stress (PII et al, 2015).…”
Section: Introductionmentioning
confidence: 99%